2018
DOI: 10.1002/chem.201801460
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Binding Site Geometry on Anion‐Binding Selectivity: A Case Study of Macrocyclic Receptors Built on the Azulene Skeleton

Abstract: An understanding of host-guest noncovalent interactions lies at the very heart of supramolecular chemistry. Often a minute change to the structure of a host molecule's binding site can have a dramatic impact on a prospective host-guest binding event, changing the relative selectivity for potential guest molecules. With the overall goal of aiding the rational design of selective and effective receptors for anions, we have studied the influence of small perturbations in binding site geometry for a series of five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…This fact has been exploited for its use in a range of colorimetric sensors. Examples include sensors for silver (Wakabayashi et al, 2013), nitrite (Murfin et al, 2020), mercury (Wakabayashi et al, 2007(Wakabayashi et al, , 2008(Wakabayashi et al, , 2012Razus et al, 2011;Birzan et al, 2017;Buica et al, 2018Buica et al, , 2019, phosphate (Lichosyt et al, 2016(Lichosyt et al, , 2018, and reactive oxygen species (Murfin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This fact has been exploited for its use in a range of colorimetric sensors. Examples include sensors for silver (Wakabayashi et al, 2013), nitrite (Murfin et al, 2020), mercury (Wakabayashi et al, 2007(Wakabayashi et al, , 2008(Wakabayashi et al, , 2012Razus et al, 2011;Birzan et al, 2017;Buica et al, 2018Buica et al, , 2019, phosphate (Lichosyt et al, 2016(Lichosyt et al, , 2018, and reactive oxygen species (Murfin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[ 43 ] Jurczak and co‐workers reported a series of azulene‐based anion receptors ( 26 – 30 ) with a macrocyclic topology and varied geometry of the binding site. [ 44 ] They revealed that macrocyclic platforms containing azulene units enable strong and selective binding of anions, determining the potential of azulene‐based receptors for sensing anions. In addition, Xiao et al.…”
Section: Azulene‐based Moleculesmentioning
confidence: 99%
“…Moreover, in aqueous media, binding of the anion may enable displacement of the so-called high-energy water from the binding cavity, which greatly enhances binding. 46–48 In spite of the considerable efforts made to create anion receptors, only a limited number of macrocyclic or cage-like structures are in use. In addition, some of them, e.g.…”
Section: Introductionmentioning
confidence: 99%